Andi Selle dalam Pergolakan Bersenjata di Sulawesi Selatan (1950-1964) - Sainal A. (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This paper describes the background, role and impact of the involvement of Andi Selle in the throes of armed in South Sulawesi. This research is a descriptive-analytic nature by using the historical method through phases of heuristics, critique, interpretation, and historiography. The involvement of Andi Selle in the throes of armed caused by internal conflict on TNI. Andi Selle was involved in a series of conflicts with several parties from the time of independence until the period before independence. The upheaval affects ethnic hatred caused by acts of violence and the monopoly of trade in the region committed soldiers, so that hurt the people of Mandar.